PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) BERBANTUAN GENIALLY UNTUK MENINGKATKAN HASIL BELAJAR MATERI KULKAS PADA SISWA KELAS XI JURUSAN TEKNIK ELEKTRONIKA SMKN 3 SINGARAJA - I Made Surya Widyananda; I Gede Ratnaya; Agus Adiarta (Jurnal Pendidikan Teknik Elektro Undiksha, 2025)
Objective of this research was to determine the increase in learning outcomes and student responses in the XI grade of Electronic Engineering at SMKN 3 Singaraja for the refrigerator (refrigerator/cooling system) topic through the application of the Problem-Based Learning (PBL) Model assisted by the Genially interactive application. Background for the research was the low learning outcomes of students on the refrigerator topic, where 75% of students scored below the Minimum Mastery Criteria (KKM) (score < 80). This was caused by a lack of engaging and interactive learning media, students' difficulty in visualizing abstract concepts like refrigeration, and limited access to practical equipment. Therefore, this study proposes a problem-based context approach through the PBL model, integrated with Genially as an interactive visual medium to boost student learning motivation and interestMethod used was Classroom Action Research (CAR), which was conducted in two cycles (Cycle 1 and Cycle 2). The research subjects were 20 students from the XI grade of Electronic Engineering. Data was collected through learning outcomes evaluation tests (formative) and a student response questionnaire. Results showed a significant increase in learning outcomes. In the initial condition (pretest), classical mastery only reached 25%. After implementing the PBL Model, which was refined in the second cycle with a focus on using Genially, classical mastery sharply increased from 10% (Cycle 1) to 100% (Cycle 2). Furthermore, student response to learning with the PBL Model assisted by Genially was highly positive, with nearly all students feeling more actively involved in problem-solving and understanding the material better in the second cycle.Conclusion of this research is that the application of the PBL Model assisted by Genially is highly effective in increasing student learning outcomes and is capable of creating an active, engaging, and studentcentered learning environment, especially for the complex refrigerator topic.